The Effect of Marketing Mix and Agricultural Incentives on Farmers' Participation in Organic Rice Cultivation in Bakti Village, Ponrang Selatan District, Luwu Regency - Iqbal M. Nur; M. Yusuf Q.; Andi Nadirah Mahmud (Yayasan Ahmar Cendekia Indonesia, 2022)
This study examines the effect of the marketing mix and agricultural incentives on farmer participation in organic rice cultivation. This research method uses descriptive quantitative research through survey techniques. The data collection uses observation and interview methods. The data were analyzed using structural equation modeling (SEM) with the help of the Smart PLS application. The results showed that the marketing mix affected farmer participation of -0.082 units with a T arithmetic value of 0.441 < 1.697 or a p-value of 0.660 > 0.005. Agricultural incentives affect farmer participation by 0.923 units with a t-count value of 3.491 > 1.697 or a p-value of 0.001 <0.05. The combined effect of the marketing mix and agricultural incentives on farmer participation is 57.2%, while 42.8% is influenced by other variables not observed in this study.